Main eco-properties of hazelnut (Corylus avellana L.) on the Sheki-Zagatala economic region - Novruz, Lala Bunyatova; Israphil, Gunay Mammadova; Allahverdi, Turkan Hasanova; Yarish, Aida Gahramanova; Maharram, Sevil Akhundova; Yashar, Gulnara Alakbarli (Institute of Advanced Engineering and Science, 2025)
The aim of the study is to determine leaf nutrients, the number of ecological-trophic groups of microorganisms and the structure of microbial communities, microbial biomass ratios, and soil parameters in the upper soil horizons in the territory of the Sheki-Zagatala economic region from five representative hazelnut gardens located in the hazelnut producing villages of Katex, Darvazbina, Boyuktala (Balakan region), and Car, Galal (Zagatala region). Has been reported that soils with slightly acidic reactions are ideal for hazelnut cultivation. Hazelnut trees in Azerbaijan have sustainable and nutritious characteristics. They grow naturally without using any chemical fertilizers and pesticides. The soil fertility of the orchards is a key factor affecting the yield and quality of nuts. The number of microorganisms at 0-15 cm in spring was 10.059·103, 7.786·103 bacterias, 3.009·103 ray fungi, and 73·103 other microscopic fungi. In moderately eroded areas, the total number of microorganisms in spring was 8.927·103, bacterias 5.895·103, ray fungi 1.874·103, and other microscopic fungi 68 103. In non-eroded fertile soils, the number of microorganisms at a depth of 0-15 cm in autumn was 8.020·103 bacteria, 5.246·103 bacteria, 1.789·103 radiant fungi, and 5.8·103 microscopic fungi. The nitrogen (N), phosphorus (P), and potassium (K) contents of tree leaves in each variant ranged from 0.49-1.07, 0.16-0.36, and 0.58-1.49%, respectively, with average values of 0.73, 0.21, and 1.03%.